NAVIGATING GENDER AND PATRIOTISM IN CAPTAIN AMERICA TRILOGY MOVIE - cut novita srikandi (Universitas Muhammadiyah Tangerang, 2019)
This articles revisits Michel Foucault and Judith Butler’s work on the gender and sexuality by examining contemporary cultural spectacles of heterosexual men, exemplified in the movie Captain America Trilogy. We will re-evaluate the queerness based on Foucault’s Sexual Discourse by thinking about the intersections between queer heroes and queer soldier. Result Show that struggle queer individuals endure with heteronormative standard culture forces them to change standard culture things and forms to create them applicable. Captain America shut relationship with Bucky provides for a queer reading and therefore the history of Captain America among the relative queer freedom caused by socio-historic conditions of war II find this queer reading during a larger queer history. And by claiming Steve Rogersand Bucky as their own queer people create space to express their identities and reaffirm the place of heroic queer people in Americanhistory which, as the descendants of that patriotic past, merits them a place within that history and within modern Americansociety.Keywords: Gender in American Society, queer heroes, gender identities